A Summary of Online Enquiries Submitted to Anti-doping Hotline 2005–2018 - Ekström, Lena; Broström, Susanne; Dahl, Marja-Liisa; Börjesson, Annica (Frontiers in Reproductive Health, 2021)
Abstract Anabolic Androgenic Steroid (AAS) abuse in the society is considered a health problem and has been associated with cardiovascular toxicity, endocrine disruption, as well as psychiatric symptoms such as aggression and cognitive dysfunction. Men and women abusing AAS, as well as persons in close relationship to AAS abusers, may encounter concerns. Subsequently, the Anti-Doping Hotline was formed 1993 to answers questions about doping in the society. Here we have reviewed 7123 enquiries posted on the Anti-Doping Hotline website between 2005-2018 to see what type of questions were raised. Most questions (n=2924) involved AAS, 60 % from abusers themselves, and 17 % from a person close to an AAS abusers. Only 2.3 % of the questions concerned AAS abusing women. Of the AAS specific questions most were from persons who sought personal advice regarding risks and side effects. Notably, the AAS abusers themselves were concerned about somatic side effects (e.g. gynecomastia) and problems related to the AAS injection. The persons in close relationship to an AAS abusers on the other hand, expressed concerns about psychiatric changes including mood swings and aggressivity. In addition to AAS, 26 and 13 % of the questions involved dietary supplements and other doping substances, respectively. A gradual decrease of questions regarding ephedrine was noted, whereas the numbers of SARMs related questions increased during this time. Our results show that there is a continuous need to provide medical, nursing, and social support and counseling to AAS abusers and their next of kin.